VII Conference/Festival Latin American Theatre Today March 26-29, 2008 -- Blacksburg, Virginia - Compton, Timothy G. (Latin American Theatre Review, 2008)
VII Conference/Festival Latin American Theatre Today March 26-29, 2008 -- Blacksburg, Virginia